2019
DOI: 10.3390/polym11081278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiber Surface Grafting with Nano-Clay on the Hydrothermal Ageing Behaviors of Flax Fiber/Epoxy Composite Plates

Abstract: Flax fiber has high sensitivity to moisture, and moisture uptake leads to the decrease of mechanical properties and distortion in shape. This paper attempts to graft flax fabric with nano-clay, with assistance from a silane-coupling agent, in order to improve hygrothermal resistance. The nano-clay grafted flax fabric reinforced epoxy (FFRP) composite produced through vacuum assisted resin infusion (VARI) process were subjected to 80% RH chamber for 12 weeks at 20, 40 and 70 °C, respectively. Moisture uptake, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 44 publications
(61 reference statements)
1
17
0
Order By: Relevance
“…This may be due to the damage of wood powder and the destruction of the interface between wood powder and polypropylene, thus affecting the transfer of stress. Compared with strength, the loss of modulus is greater, that is, the stiffness of the composite samples is very sensitive to water, which can not only confirm the damage of water on wood powder and the interface of composites but also prove that water has a plasticizing effect on the polymer matrix [16,23,28,34,35]. However, compared with the modulus of pure polypropylene, the modulus value of wood powder reinforced polypropylene composites is still relatively high.…”
Section: Dynamic Mechanical Analysis Of the Compositesmentioning
confidence: 96%
See 1 more Smart Citation
“…This may be due to the damage of wood powder and the destruction of the interface between wood powder and polypropylene, thus affecting the transfer of stress. Compared with strength, the loss of modulus is greater, that is, the stiffness of the composite samples is very sensitive to water, which can not only confirm the damage of water on wood powder and the interface of composites but also prove that water has a plasticizing effect on the polymer matrix [16,23,28,34,35]. However, compared with the modulus of pure polypropylene, the modulus value of wood powder reinforced polypropylene composites is still relatively high.…”
Section: Dynamic Mechanical Analysis Of the Compositesmentioning
confidence: 96%
“…It is known that the mechanical properties of the natural fiber-reinforced polymer composites can be improved by the modification of fibers or polymers [26,27]. What is more, several efforts have shown that the modification of the interface between natural fibers and polymers can also reduce the degradation effect of moisture on some mechanical properties [15,28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, fiber reinforced polymer plates have been widely used as strengthening materials of concrete members [2][3][4][5]. The long-term performance of FRP materials in harsh environments such as hygrothermal or alkaline environments is significant for their application [1] and has been widely investigated [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the addition of nano or micro additive as filler in natural fibre reinforced composite is investigated in several papers [ 6 , 7 , 8 , 9 ].…”
mentioning
confidence: 99%
“…On the bases of the experimental data, the authors state that these simple treatments, potentially prone to further optimization, can represent a step toward producing natural fibre composites with mechanical profiles compatible with semi-structural applications. Similarly, Wang et al [ 8 ] improved the hygrothermal resistance of flax fibre reinforced epoxy composites through grafting flax fabric with nanoclay. In more detail, the introduction of nano-clay reduces both moisture uptake and the coefficient of diffusion of composites that show better dimensional stability than the untreated ones.…”
mentioning
confidence: 99%